KONFLIK ANTARA MASYARAKAT SIULAK MUKAI DENGAN SIULAK GEDANG KECAMATAN SIULAK PROVINSI JAMBI TAHUN (2006-2009) - Pratama, Yoanda Okta (Pendidikan Sejarah, 2014)
This research study about society conflict that happened between Siulak Mukai and SiulakGedang in the form of hardness ( ruining and combustion). This research is executed in SiulakMukai and Siulak Gedang in district of Siulak, Sub-Province of Kerinci, Provinsi Jambi. Target ofthis Research for: How the background the happening of in Siulak Mukai with Siulak Gedang,How the conflict that happened between Siulak Mukai with Siulak Gedang, and How affect fromconflict that happened between Siulak Mukai and of Siulak Gedang in the year 2006-2009.Method Research which is applied in this research represent method research of history,Heuristic, collecting from source of source and primary of secunder, than criticize to source ofinternal criticism goodness and also criticism of eksternal, afterthat analyse and interpretation, andthe final phase of Historiografi or writing matching with method research of history. As fortechnique performed within this research by interview and documentation.From result of research can be concluded that 1) Conflict appearance between SiulakMukai with Gedang Siulak because character and grudge of society of Siulak Mukai and of SiulakGedang very Hard, which formed by background tradition of beludai. Vindictive between SiulakMukai and of Siulak Gedang bubble up to through conflict that happened between Siulak Mukaiand of Siulak Gedang which triggered by problem of conflict of worker of ojek in fighting overpassenger, and also slapped around by society of Siulak Mukai to young man of Siulak Gedang.Form Conflict that happened between Siulak Mukai with Siulak Gedang represent action throwstone 2) On 06 mei 2006 Top conflict happened when citizen of Siulak Mukai burn House citizenof Siulak Huge amount to 43 burnt house and 56 damage house 3) Social affect of conflict,existence of title to citizen of Siulak Mukai as " Tukang Sundun", with the meaning worker burn,other social area dissolution between family, like remained by child is father 4) The conflictfinished by deliberation mediated by custom clan, governance, and police.